2019
DOI: 10.12669/pjms.36.icon-suppl.1721
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease in childhood B Lymphoblastic Leukemia and its correlation with other risk factors

Abstract: Objective: To determine frequency of post induction and post consolidation minimal residual disease (MRD) in pediatric B-lymphoblastic leukemia (B-ALL) patients and its association with clinical risk factors. Methods: This is a retrospective, cross sectional study carried out at the Indus Hospital on paediatric patients (1-17 years) was performed from May 2015 to January 2018. On day 35, MRD testing was done on bone marrow aspirate using 4 color flow cytometer with 0.01% cut off. Positive cases were rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
1
3
1
2
Order By: Relevance
“…In the current study, our results of (MRD) of ALL patients at EOI revealed that out of our 93 patients 64 (70%) had negative MRD and 14 (30%) had positive MRD. This is in line with the result from Maraj et alwho found that 63.3% of ALL patients achieved negative MRD after finishing induction chemotherapy (Meraj et al,2020) Furthermore, a pediatric study by Children's Oncology Group reported that 28.6% end induction MRD positivity (Borowitz et al,2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, our results of (MRD) of ALL patients at EOI revealed that out of our 93 patients 64 (70%) had negative MRD and 14 (30%) had positive MRD. This is in line with the result from Maraj et alwho found that 63.3% of ALL patients achieved negative MRD after finishing induction chemotherapy (Meraj et al,2020) Furthermore, a pediatric study by Children's Oncology Group reported that 28.6% end induction MRD positivity (Borowitz et al,2003).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, cytogenetic abnormalities characteristic of B-ALL mainly determine the diseases biology, affect prognosis, and guide therapy (Meraj et al,2020). Cytogenetic test by Fluorescence In Situ Hybridization (FISH) was done for 54 of our patients t (9:22, t12:21,11q23).…”
Section: Discussionmentioning
confidence: 99%
“…Дальнейшее изучение прогностического влияния МОБ на частоту рецидивов и показатели выживаемости позволит дополнить существующие критерии групп риска и своевременно оптимизировать программную терапию: интенсифицировать лечение за счет применения «блоковой» программы, включить таргетные препараты (блинатумомаб) и определить дополнительные показания к проведению алло-ТГСК с учетом прогностического значения МОБ на постиндукционном этапе лечения [5,6].…”
Section: заключениеunclassified
“…In addition to the National Cancer Institute (NCI) based risk factors of age and white cell count, disease immunophenotype (B-cell versus T-cell), central nervous system (CNS) involvement, treatment response, and cytogenetic aberrations are the key determinants of disease outcome. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%